Acute disseminated encephalomyelitis following Mycoplasma pneumoniae infection complicated by respiratory arrest due to concurrent bilateral lateral medullary lesions: A case report. Issue 5 (24th July 2018) - Fukuoka, Takuya; Nakazato, Yoshihiko; Kawasaki, Hitoshi; Ikeda, Kei; Yamamoto, Toshimasa
Abstract: Reports on concurrent bilateral lateral medullary lesions in patients with neurological disorders are lacking. Herein, we discuss the case of a 40‐year‐old man who developed acute disseminated encephalomyelitis due to Mycoplasma pneumoniae infection. Brain magnetic resonance imaging revealed high signal intensities and demyelination in the concurrent bilateral lateral medulla and cervical spinal cord. Clinical features included respiratory arrest and psychiatric symptoms, although his symptoms improved several months following the initiation of artificial respiration and repeated steroid pulse therapy. Such findings emphasize the need to carefully monitor patients with acute disseminated encephalomyelitis exhibiting concurrent bilateral medullary lesions due to the risk of sudden respiratory arrest.